2017
DOI: 10.1016/j.ajpath.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Type II Natural Killer T Cells that Recognize Sterol Carrier Protein 2 Are Implicated in Vascular Inflammation in the Rat Model of Systemic Connective Tissue Diseases

Abstract: We previously generated a rat model that developed systemic connective tissue diseases, including synovitis, myositis, and small-vessel vasculitis (SVV), and established a vascular endothelial cell-reactive T-cell clone, VASC-1, from the model. VASC-1 was determined to be a type II natural killer T-cell clone. In this study, we attempted to identify the antigen recognized by VASC-1. The monkey-derived cell line COS-7 was used because VASC-1 does not bind naturally to COS-7, although the amino acid sequences ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In a subsequent study, a more potent phosphatidylglycerol antigen from Listeria monocytogenes was identified that had a structure distinct from previously identified mammalian or microbial variants, as it contains short, fully saturated anteiso fatty acid lipid tails (32). Type II NKT cells may not only recognize lipid antigens but a recent study suggests that they also can recognize hydrophobic peptides presented on CD1d (33, 34). A report by Nishioka et al found that a rat type II NKT cell clone, reactive to vascular endothelial cells, could recognize a CD1d-presented hydrophobic peptide derived from sterol carrier protein 2, a protein implicated in intracellular lipid transfer.…”
Section: Antigens For Type II Nkt Cellsmentioning
confidence: 99%
“…In a subsequent study, a more potent phosphatidylglycerol antigen from Listeria monocytogenes was identified that had a structure distinct from previously identified mammalian or microbial variants, as it contains short, fully saturated anteiso fatty acid lipid tails (32). Type II NKT cells may not only recognize lipid antigens but a recent study suggests that they also can recognize hydrophobic peptides presented on CD1d (33, 34). A report by Nishioka et al found that a rat type II NKT cell clone, reactive to vascular endothelial cells, could recognize a CD1d-presented hydrophobic peptide derived from sterol carrier protein 2, a protein implicated in intracellular lipid transfer.…”
Section: Antigens For Type II Nkt Cellsmentioning
confidence: 99%
“…In our earlier study, we identified rSCP2 518-532 , FFQGKLKIAGNMGLA, as the epitope, which was recognized by one of rat CD1d-restricted type II NKT cells (10). In this study, we attempted to detect human CD1d-restricted type II NKT cells in peripheral blood using hSCP2 518-532 , FFQGPLKITGNMGLA, the human counterpart of rSCP2 518-532, together with a CD1d tetramer in flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the association of impaired CD1drestricted type II NKT cells with inflammatory diseases has also been reported. Recently, we identified P 518-532 of rat sterol carrier protein 2 (rSCP2 518-532 ), FFQGKLKIAGNMGLA, as the epitope, which was recognized by one such CD1d-restricted type II NKT cell (10). In addition, we have shown that proinflammatory autologous vascular endothelial cell-reactive CD1d-restricted type II NKT cells were involved in the development of vasculitis in rats (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although they did not declare the subtype of type II collagen-reactive CD1d-restricted NKT cells in the paper, it appears to be a type II phenotype in terms of the antigen property. More recently, our group demonstrated that the hydrophobic peptide derived from sterol carrier protein 2 (SCP2), an intracellular lipid transporter, could be presented by CD1d and then recognized by CD1d-restricted type II NKT cells ( 25 ). Girardi et al conducted X-ray analyzes of binding formation of CD1d and peptide antigens ( 26 ).…”
Section: Antigens Recognized By Cd1d-restricted Type II Nkt Cellsmentioning
confidence: 99%